TRENDS IN THE DEVELOPMENT OF DARK TOURISM IN UKRAINE AMIDST THE RUSSIAN-UKRAINIAN WAR - PANKIV, Natalia; VELYCHKO, Tetyana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the conceptual foundations, evolution, and current trends of dark tourism as a specific form of cultural and memorial travel that reflects humanity’s attitude toward death, tragedy, and historical trauma. The authors analyze the theoretical approaches to defining dark tourism and provide its detailed classification into main subtypes—disaster tourism, mystical tourism, thanatourism, and necropolitan tourism—revealing their distinctive motivational, cultural, and ethical dimensions. Based on international experience, the paper examines the development of dark tourism in countries that have undergone wars and catastrophic events, including Japan, Bosnia and Herzegovina, and Egypt, identifying key patterns of post-war reconstruction and memorialization. Special attention is paid to the prospects for developing dark tourism in Ukraine under the conditions of the Russian-Ukrainian war. The study highlights how war has intensified interest in places of collective trauma—battlefields, destroyed cities, and memorial sites—transforming them into symbolic spaces for preserving historical truth, fostering national identity, and raising global awareness of Ukraine’s struggle. The article also assesses the potential of Ukrainian locations such as the Chernobyl Exclusion Zone, the Babyn Yar memorial, Lychakiv and Baikove cemeteries, and the National Museum of the Holodomor as core destinations for ethically oriented dark tourism. An original author’s tour, “The Threshold of the Invisible: Between Memory and Radiation,” is presented as a model for sustainable and safe development of this niche, combining educational, memorial, and emotional experiences. The study emphasizes that the successful formation of dark tourism in Ukraine requires an integrated strategy encompassing ethical, cultural, economic, and social aspects, as well as the establishment of legal frameworks, safety standards, and international cooperation. The findings confirm that dark tourism, if approached responsibly, can serve as an instrument of collective memory, reconciliation, and cultural resilience in the post-war recovery of Ukraine.
Keywords: dark tourism; Ukraine; war; post-war period; tourist site; tourism activity; history